Histoplasmosis Presenting as Granulomatous Hepatitis: Case Report and Review of the Literature - Nancy A. Rihana; Manasa Kandula; Ana Velez; Kumud Dahal; Edward B. O’Neill (Case Reports in Medicine)
Background. Histoplasma capsulatum is the most common endemic mycosis in the United States and is a frequent cause of opportunistic infection in immunodeficient hosts. Histoplasmosis is most often self-limiting and goes unrecognized in the immunocompetent population but can progress to disseminated histoplasmosis in patients with an impaired immune system. Liver involvement as a part of disseminated histoplasmosis which usually originates in the lung is well known. However, extrapulmonary hepatic histoplasmosis as a primary manifestation is extremely rare. Case Presentation. We report a rare case of histoplasmosis that presented as persistent fever and abnormal liver function tests in a 66-year-old female with rheumatoid arthritis, receiving infliximab. Conclusion. Emphasizing histoplasmosis as a major cause of acute granulomatous hepatitis and fever of unknown origin in cell mediated immunodeficient population, this case highlights the need for high index of suspicion and the importance of prompt diagnosis since any delay of treatment can be life threatening in this population.